2016
DOI: 10.18632/oncotarget.13842
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on factors affecting the prognosis of oral cancer in a Chinese population

Abstract: This study was performed to identify the factors affecting prognosis of oral cancer patients. 1240 pathologically confirmed oral cancer patients were included. The sociodemographic and clinical characteristics of all patients were collected. Univariate and multivariate Cox proportional hazards models were used to assess potential prognostic factors for survival. 1240 oral cancer patients were followed up for 49235.00 person months, and the 5-year overall survival rate was 64.38%. Both univariate and multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…BMI is the main tool for nutritional status assessment in clinical. Multiple studies have demonstrated that a low BMI was an independent predictor of a poor prognosis in oral cancer [9,12]. Our study also confirmed that patients with BMI < 18.5 kg/m 2 had significantly worse prognosis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…BMI is the main tool for nutritional status assessment in clinical. Multiple studies have demonstrated that a low BMI was an independent predictor of a poor prognosis in oral cancer [9,12]. Our study also confirmed that patients with BMI < 18.5 kg/m 2 had significantly worse prognosis.…”
Section: Discussionsupporting
confidence: 86%
“…Traditional nutritional indicators such as body mass index (BMI) and serum albumin (ALB) have been widely used in clinical to assess the nutritional status of the cancer patients and have been shown to be associated with the prognosis of a variety of tumors such as rectal cancer, head neck, oral cancer and gynecologic malignancies [9][10][11][12][13]. In addition to BMI and ALB, two comprehensive indicators prognostic nutritional index (PNI) which includes albumin and lymphocyte and nutritional risk index (NRI) which combines weight, height and serum albumin levels, have also been reported as simple but sensitive methods that can objectively assess the nutritional status of cancer patients and predict their prognosis in esophageal squamous cell carcinoma, liver cancer, lung cancer, and gastric cancer et al [11,[14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor‐node‐metastasis (TNM) stage is a traditional indicator and widely used for predicting the prognosis of OSCC in routine clinical practice. Several previous studies demonstrated that other tumor‐related factors (such as tumor volume, differentiation, the depth of invasion, and so on) could also affect the survival of OSCC . In addition, various biomarkers in serum, including neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and prognostic nutritional index, have also been identified previously .…”
Section: Introductionmentioning
confidence: 96%
“…Several previous studies demonstrated that other tumor-related factors (such as tumor volume, differentiation, the depth of invasion, and so on) could also affect the survival of OSCC. 5,6 In addition, various biomarkers in serum, including neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and prognostic nutritional index, have also been identified previously. [7][8][9] However, a single factor has limited effect for accurately predicting cancer prognosis, and it is therefore essential to integrate several valuable indicators for a more precise prediction of OSCC prognosis.…”
mentioning
confidence: 98%
“…Tongue is considered as the most frequently affected site, followed by gingiva, buccal mucosa, floor of mouth, palate and lip, and occasionally found in retromolar area or other oral sites [ 2 ]. Furthermore, survival varies in relation to tumor sites in origin [ 3 ]. Thus, it is essential to assess site-specific risk factors for OSCC.…”
Section: Introductionmentioning
confidence: 99%